Advantages and disadvantages of distance teaching in foreign language education during COVID-19 - Kruse, Irina; Lutskovskaia, Larisa; Stepanova, Valentina V. (Frontiers in Education, 2022)
This article aimed to analyze the identified advantages and disadvantages of distance education in foreign language teaching in the transition to distance learning due to the COVID -19 pandemic. The data were collected through questionnaires and observations. A total of 298 university students participated in the research. The results of this research show that 1- the quality parameters of the changes and additions to the curriculum of foreign language teaching, 2- the final evaluation of the students in these subjects conducted in distance learning compared to the results shown in the offline form, 3- the satisfaction of the students with the electronic format of academic subjects, and 4- the formation of communicative competences under the changed learning conditions. The results are based not only on the final grades in the control sections in written and oral form but also on the emotional evaluation of the distance format teaching units in foreign languages. In addition, the results have shown that a complete transition to distance education is possible at COVID as a contingency measure. The research results will help to solve problematic issues related to the organization of the educational process and the need to comply with sanitary regulations.